The Sketch of Reading Instruction in Islamic Tertiary Level of Education - Andang Saehu; Annie Susany Somantri (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2017)
This study briefly reports classroom observations in one of EFL classes at English Studies Department of Islamic Tertiary Level of Education in Bandung, Indonesia. The focus of the class was on Literal Reading. The classroom observations were conducted in five class periods consecutively. Having studied what was happening to the students, using a qualitative case study, the data collected through observation checklist and interview guide found that the lecturer designed various activities in teaching Literal Reading in the EFL class. The lecturer applied teaching activities in three stages: pre-reading, while-reading, and post-reading. The activities in the pre-reading were aimed at activating students’ schemata, generating students’ interest and trying to anticipate any difficult vocabularies. The while-reading stage is to invite students to be involved at phonic method and mapping concept strategy. The post-listening stage is to internalize what they have read with other language skills (e.g. writing and speaking) and to check students’ comprehension.